The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1021/bi100664s
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Surface Hydrophobicity of the Cataract-Associated P23T Mutant of Human γD-Crystallin Is Responsible for Its Dramatically Lower, Retrograde Solubility

Abstract: The cataract-associated Pro23 to Thr (P23T) mutation in human γD-crystallin (HGD) has a variety of phenotypes and is geographically widespread. Therefore there is considerable interest in understanding the molecular basis of cataract formation due to this mutation. We showed earlier [Pande, et al. (2005) Biochemistry 44, 2491-2500] that the probable basis of opacity in this case is the severely compromised, retrograde solubility and aggregation of P23T relative to HGD. The dramatic solubility change occurs eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(72 citation statements)
references
References 28 publications
3
69
0
Order By: Relevance
“…S2B), the Bis-ANS data show a small increase in the net surface hydrophobicity for E107A compared to HGD, while Nile Red does not. Because Bis-ANS is known to be a more sensitive probe for surface hydrophobicity compared to Nile Red (28), this difference is not surprising. The slight increase in surface hydrophobicity is consistent with the substitution of Glu by Ala in the mutant.…”
Section: Resultsmentioning
confidence: 99%
“…S2B), the Bis-ANS data show a small increase in the net surface hydrophobicity for E107A compared to HGD, while Nile Red does not. Because Bis-ANS is known to be a more sensitive probe for surface hydrophobicity compared to Nile Red (28), this difference is not surprising. The slight increase in surface hydrophobicity is consistent with the substitution of Glu by Ala in the mutant.…”
Section: Resultsmentioning
confidence: 99%
“…Further, NMR-spectroscopy and X-ray crystallography have indicated that the Pro24 and Thr24 proteins are structurally similar overall [21,22]. However, the Thr24 mutant exhibits local conformational and dynamic differences that may initiate aggregation or polymerization and in vitro experiments have shown that the Thr24 protein exhibits reduced solubility-a property that is likely to trigger cataract formation [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…For example, in γD-, replacing the residue P24 with T (or other residues such as S or V), as reported in detail by the Pandes [56][57][58][59][60], decreases the solubility of the protein by increasing hydrophobicity and restricting backbone flexibility, altering the temperaturedependent solubility and the phase diagram. The roles of other amino acids in the sequence, whose replacement is associated with lens malfunction, are yet to be understood.…”
Section: Section Ii: Mutations In Human γ-Crystallins and Pathologymentioning
confidence: 99%